Three rooted, four canalled mandibular first molar (Radix Entomolaris) - Parolia, A; Kundabala, M; Thomas, MS; Mohan, M; Joshi, N (Kathmandu University Medical Journal, 2010)
A mandibular first molar with two distal roots is an interesting example of anatomic variation. This paper describes case reports of mandibular first molar with three roots (one mesial and two distal) and four canals (two in mesial and one in each distobuccal and distolingual root). The canals were shaped with protaper rotary files and irrigated with 5.25% sodium hyochlorite, 0.2 %w/v of chlorhexidine gluconate and normal saline as the final irrigant. The canals were then obturated with gutta- percha and AH plus sealer. These case reports show an anatomic variation of internal morphology of the tooth and points out the importance of searching for additional canals. Key words: Mandibular first molar; two distal roots; four canals DOI: 10.3126/kumj.v7i3.2739 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 289-292